Effect of Dopant Compensation on the Behavior of Dissolved Iron and Iron-Boron Related Complexes in Silicon. (30th August 2015) - Zhu, Xiaodong; Yu, Xuegong; Chen, Peng; Liu, Yong; Vanhellemont, Jan; Yang, Deren
Abstract : The behavior of iron, iron-boron (FeB) pairs, and iron-boron-phosphorus (FeB-P) complexes has been studied in B-doped Czochralski silicon with phosphorus (P) compensation and compared with that in uncompensated material. The interstitial iron concentration has been measured at temperatures from 50 to 270°C. The apparent binding energy (E b ) of FeB in compensated silicon is (0.25 ± 0.03) eV, significantly lower than the (0.53 ± 0.02) eV in uncompensated silicon. Possible reasons for this reduction in binding energy are discussed by experimental and calculation methods. The results are important for understanding and controlling the behavior of Fe in compensated silicon.